Antibacterial and Antifungal Screening of the Root Extracts of Nardostachys}atamansi (Biological Sciences - PJSIR, 2007)
A nti microbi al activity of ethanol, eth y l acetate and hex ane extracts of Nardos/achys jalaman si roots were stu died in  vilro again st si x  path ogen i c gram  pos i tive  bacteria ( Slayphylococcu s  aureus, Slreplococcus  in/ermedius, S faecalis,  Ba cillus pumilus ,  B. cereus,  B. sublilus),  six gram  negative bacteri a ( Escherichia  coli,  Salmonella  typhi,  S paralyphi  B, Klebsiella pn eumo11iae, Proteus  mirabilus,  Slzigella jlexneri )  and  five  fu ngi  (Trichophylon  rubru111, T schoenleinii, Aspe rgillus 11ige1; Candida albicans, C glabrata ) . Ethanol ic root extract ex hi bited max i mum antimicro bial activ i ty aga i n st al l the tested bacteria and fu ngi , at concentrations of 5, I O and 20 mg/ ml as compared to ethyl acetate an d hexane extract, wh ich d id not show marked activity. A n ti m icrobia l acti vity was com pared wi th the acti vi ties of standard anti bacteria l and an tifu n gal d rugs, name l y Am pic i l l i n and Nystati n , respectivel y. Th e m i n i mu m i n h i bi tory con centrations (MIC) were between 0.5- 1 mg/ ml agai nst a ll the stud ied microor ganisms.